Shear wave transmissivity measurement by color Doppler shear wave imaging. (21st June 2016) - Yamakoshi, Yoshiki; Yamazaki, Mayuko; Kasahara, Toshihiro; Sunaguchi, Naoki; Yuminaka, Yasushi
Abstract: Shear wave elastography is a useful method for evaluating tissue stiffness. We have proposed a novel shear wave imaging method (color Doppler shear wave imaging: CD SWI), which utilizes a signal processing unit in ultrasound color flow imaging in order to detect the shear wave wavefront in real time. Shear wave velocity is adopted to characterize tissue stiffness; however, it is difficult to measure tissue stiffness with high spatial resolution because of the artifact produced by shear wave diffraction. Spatial average processing in the image reconstruction method also degrades the spatial resolution. In this paper, we propose a novel measurement method for the shear wave transmissivity of a tissue boundary. Shear wave wavefront maps are acquired by changing the displacement amplitude of the shear wave and the transmissivity of the shear wave, which gives the difference in shear wave velocity between two mediums separated by the boundary, is measured from the ratio of two threshold voltages required to form the shear wave wavefronts in the two mediums. From this method, a high-resolution shear wave amplitude imaging method that reconstructs a tissue boundary is proposed.